Transposon mutagenesis as an approach to improved understanding of Borrelia pathogenesis and biology - Lin, Tao; Troy, Erin B.; Hu, Linden T.; Gao, Lihui; Norris, Steven J. (Frontiers in Cellular and Infection Microbiology, 2014)
Transposon insertion provides a method for near-random mutation of bacterial genomes, and has been utilized extensively for the study of bacterial pathogenesis and biology. This approach is particularly useful for organisms that are relatively refractory to genetic manipulation, including Lyme disease Borrelia. In this review, progress to date in the application of transposon mutagenesis to the study of Borrelia burgdorferi is reported. An effective Himar1-based transposon vector has been developed and used to acquire a sequence-defined library of nearly 4,500 mutants in the infectious, moderately transformable B. burgdorferi B31 derivative 5A18NP1. Analysis of these transposon mutants using signature-tagged mutagenesis (STM) and Tn-seq approaches has begun to yield valuable information regarding the genes important in the pathogenesis and biology of this organism.